Effect of quercetin on muscle growth and antioxidant status of the dark sleeper Odontobutis potamophila - Zhu, Chenxi; Liu, Guoxing; Gu, Xiankun; Yin, Jiawen; Xia, Aijun; Han, Mingming; Zhang, Tongqing; Jiang, Qichen (Frontiers in Genetics, 2022)
Quercetin is a flavanol beneficial in reducing fat, promoting muscle growth and Anti-oxidation. To study its effects in freshwater fish, the full-length cDNA of the follistatin (FST) and myostatin (MSTN) genes of the dark sleeper Odontobutis potamophila were cloned for the first time. The complete mRNA sequences for FST and MSTN were submitted to GenBank with accession numbers OK641659 and OK641660, respectively. Mature individual O. potamophila were exposed to quercetin at one of four concentrations (0, 2.5, 5 and 10 mg/L) for 21 days. The expression level of MSTN in the quercetin solution was lower than in the unexposed control group. while that genes of promoting muscle growth like FST, Myf5(myogenic)factor 5, MyoD (myogenic differentiation), MyoG (myogenin), and TGF-β1 (transforming growth factor-beta 1) were higher than in the control group. Apolipoprotein and growth hormone receptor transcription levels in the quercetin-treated fish were significantly lower than in the control group. The concentrations of triglyceride, low-density lipoprotein cholesterol and high-density lipoprotein cholesterol in the muscle tissue decreased, and the lipid-lowering function of quercetin was also demonstrated at the biochemical level. In this study, we analyzed the mRNA levels of AKT, Keap1 (kelch-like ECH-associated protein 1), Nrf2 (NF-E2-related factor 2) oxidation-related genes and antioxidant enzyme glutathione (GSH) in the Nrf2/ARE antioxidant pathway after quercetin treatment. Malondialdehyde (MDA) and catalase (CAT) in the hepatopancreas of O. potamophila, demonstrating that quercetin has antioxidant properties. The results showed that quercetin has no significant effects on the growth performance of O. potamophila, but is effective in increasing muscle-growth and lowering muscle fat content.